NO SMOKING IN THE WORKPLACE - ANKNER WD (Tufts Archival Research Center, 2007)
Missing Attachments; Memo from William D Anker banning smoking in the Rhode Island Department of Transportation Headquarters office building. Cites health hazards of secondhand smoke as reason for the ban. Lists numbers to call for information on smoking cessation.